O papel do Programa Nacional de Alimentação Escolar - PNAE para a inserção da agricultura familiar em novos mercados: o caso da COOPAFI - Capanema - Valandro, Keila (2014)
This research evaluates the contribution of the National School Feeding Programme (PNAE) in creating new markets for local producers to the experience of cooperative COOPAFI the municipality of Capanema, an organization that is a reference in many strategies to access the institutional market to enable the marketing of products of its affiliated farmers, but: Did the PNAE positively impacted the revenue from these farmers? Where and how the farmers to sell their products if they were not associated with the cooperative? Therefore, the first hypothesis is that farmers who access the PNAE in the municipality of Capanema had effective increase income. And the second is that farmers would have no other means to achieve market in the local / regional market in close or similar amount if they were not members. This way will be sought to understand the role of PNAE in strengthening family agriculture and its organizations. In particular, efforts will be made: (1) investigate the reasons for accession and farmers remain in the PNAE and understand how farmers were inserted in PNAE; (2) verify that the PNAE helped improve the living conditions of the population involved; (3) identify which foods purchased by COOPAFI - Capanema in meeting their local / regional demands to understand the motivations and perceptions thereof forward the possibility of generating income not only in the short term; (4) describe the socioeconomic profile of participants PNAE farmers and the influence of this policy on the integration of family farmers in new markets. The survey found an effective increase in revenue among the cooperative, which highlights the role of PNAE in strengthening family farming, however, was not possible to characterize the extreme dependence of farmers to the cooperative, but an insert into new markets that led to the diversification production; increase in the quantity produced; the qualification of the farmer to improve the quality of products; the specialization of labor in the agricultural industry and the knowledge of new marketing channels.